Fixing Blood Alkalinity by Using Apium Graveolens as Treatable Strategy to Prevent Covid 19 Likes Infection - Abdul-Samad Uleiwi Hassan; Manal Abd Alwahed Alssirag; Sameer Mageed Alatar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Juice of fresh celery solution will be given to domestic cats and normal cases of human to achieve thepurposes of this project. Dosages given three times a day/one weeks in a mount of one cup 250 ml for human143 lb, and cats 10 lb in amount of one spoon 15 ml for each. Later, blood O2, CO2 and alkalinity Evaluatedto get results.Our study conclusion were proves the high ability of the celery juice’s antioxidants compounds to relievethe high acidity of blood resulted from viral infections like covid 19 and influenza, in a way to curing andstrengthening the immune system against those viral infecions.